Event-related brain potential correlates of prospective memory in symptomatically remitted male patients with schizophrenia - Chen, Guoliang; Zhang, Lei; Ding, Weiyan; Zhou, Renlai; Xu, Peng; Lu, Shan; Sun, Li; Jiang, Zhongdong; Li, Huiju; Li, Yansong; Cui, Hong (Frontiers in Behavioral Neuroscience, 2015)
Prospective memory (PM) refers to the ability to remember to perform intended actions in the future. Although PM deficits are a prominent impairment in schizophrenia, little is still known about the nature of PM in symptomatically remitted patients with schizophrenia. To address this issue, event-related brain potentials (ERPs) were recorded from 20 symptomatically remitted patients with schizophrenia and 20 healthy controls during an event-based PM paradigm. Behavioral results showed that symptomatically remitted patients with schizophrenia performed poorly on the PM task compared with healthy controls. On the neural level, the N300, a component of the ERPs related to PM cue detection, was reliable across these 2 groups, suggesting a degree of functional recovery of processes supporting cue detection in patients with symptomatically remitted schizophrenia. By contrast, the amplitude of the prospective positivity, a component of the ERPs related to PM intention retrieval, was significantly attenuated in symptomatically remitted schizophrenia patients relative to healthy controls. Furthermore, a significant positive correlation between the amplitude of the prospective positivity and accuracy on the PM task was found in those patients, indicating that patients’ poor performance on this task may result from the failure to recover PM cue-induced intention from memory. These results provide evidence for the existence of altered PM processing in patients with symptomatically remitted schizophrenia, which is characterized by a selective deficit in retrospective component (intention retrieval) of PM. Therefore, these findings shed new light on the neurophysiological processes underlying PM in schizophrenia patients during clinical remission.